Очень страшная история и другие повести - Алексин Анатолий Георгиевич (Детская литература, 1987)
Экземпляры: ФО-3 (1988) / Инвентарный номер: 17043 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 48 / ББК: 84(2Рос=Рус)6